The rhetoric of adaptive reuse or reality of demolition: Views from the field - Bullen, Peter; Love, Peter (Elsevier, 2010)
The City of Perth in Western Australia is a relatively modern city and was founded in 1829. A considerable amount of its built stock will become redundant in the near future. An issue that will face many building owners, designers, property developers and planners will be to adapt or demolish existing buildings to meet changing economic and social needs and issues related to sustainability. The rhetoric associated with the benefits of adaptive reuse has been widely espoused. It would appear in reality; however, that owners and practitioners are only embracing this sustainability strategy in a piecemeal manner within Perth. This paper examines owners’ and practitioners’ views and experiences associated with adaptive reuse. In conjunction with the normative literature and the research findings, a building viability process model is presented that can be used by owners, occupiers and planners to determine the strategy needed to meet changing commercial and regulatory demands being required of buildings.